Lack of cross-reactivity between antibody against smooth muscle and antibodies to measles virus in sera from patients with chronic active hepatitis. - Sommer, A I (1982)
A majority of patients with HBsAg-negative chronic active hepatitis (CAH) show considerably raised titres of serum antibodies against measles virus antigens. Since these patients often have high titers of antiactin specific antibodies against smooth muscle, and since actin is also incorporated into the measles virion during replication, we have examined whether there was any cross-reactivity between the two antigen-antibody systems. Cross-absorptions of sera from patients with CAH were performed using measles virus antigens and smooth muscle from human uterus. The corresponding specific antibodies were removed from serum without significantly affecting the titres of the other antibodies. Absorption had no influence on the total amount of IgG in serum. The raised titres of antibodies against measles virus seen in CAH can therefore not be explained by cross-reaction with antibodies to smooth muscle.